2021
DOI: 10.3390/nano11092462
|View full text |Cite
|
Sign up to set email alerts
|

Stable Fluorescence of Eu3+ Complex Nanostructures Beneath a Protein Skin for Potential Biometric Recognition

Abstract: We designed and realized highly fluorescent nanostructures composed of Eu3+ complexes under a protein coating. The nanostructured material, confirmed by photo-induced force microscopy (PiFM), includes a bottom fluorescent layer and an upper protein layer. The bottom fluorescent layer includes Eu3+ that is coordinated by 1,10-phenanthroline (Phen) and oleic acid (O). The complete complexes (OEu3+Phen) formed higher-order structures with diameter 40–150 nm. Distinctive nanoscale striations reminiscent of fingerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A very different use of PiFM was demonstrated by Zhao et al studying Eu 3+ nanostructures as a potential system for biometric recognition. 61 The Eu 3+ /oleic acid complexes were placed under a protein skin and their chemical composition and morphology studied with PiFM using the amide II band at 1540 cm À1 , and the OEu 3+ Phen complex carboxyl band at 1663 cm À1 , Fig. 11.…”
Section: Biological Surfacesmentioning
confidence: 99%
“…A very different use of PiFM was demonstrated by Zhao et al studying Eu 3+ nanostructures as a potential system for biometric recognition. 61 The Eu 3+ /oleic acid complexes were placed under a protein skin and their chemical composition and morphology studied with PiFM using the amide II band at 1540 cm À1 , and the OEu 3+ Phen complex carboxyl band at 1663 cm À1 , Fig. 11.…”
Section: Biological Surfacesmentioning
confidence: 99%
“…According to previous reports, the coordination environment of Eu 3+ ions in Eu:HA may be changed through the interaction with organic molecules. Citric acid (Cit) is an organic acid containing three carboxyl groups with a strong coordination ability (i.e., formation of the chelates) with various metal ions, which can effectively coordinate with lead­(II) and cadmium­(II) ions , and can also coordinate with calcium­(II), terbium­(III), and europium­(III) ions for immobilizing various crystal surfaces. In addition, the inhibition of crystal growth and the enhancement of crystal solubility occurred through the coordination effect, and the dissolution–reprecipitation processes of the crystals are strongly related to ion replacement. , Moreover, it was suggested that Cit coordination could promote the replacement state change of Eu 3+ ions in HA. Furthermore, our group has elucidated the interactions between Cit and Eu:HA, which suppressed the photoluminescence (PL) deactivation caused by the adsorption of surface water molecules. Thus, the control of the Cit coordination behavior can change the PL properties of the Eu 3+ ions in HA.…”
Section: Introductionmentioning
confidence: 99%